Lecturer’s talk in Classroom interaction in Listening class: A case study - Muhammad Zuhri Dj; Musfirah Musfirah (Loquen, 2020)
The aim of this research was to find out the category of lecturer’s talk in classroom interaction in learning listening. The method used a case study which applied observation and interview. It aimed to gain the data that were observed during Teaching and learning process and interview the lecturer and learners. The data were presented by analyzing the lecturer’s talk. The source of data was the lecturer who teaches listening in TBI program. The instrument of this research were observation where the researcher saw or watched the teaching and learning process after that transcribing the lecturer’s talk and interview where the researcher used recorder. This research instrument was applied to acquire the data about lecturer’s talk used by the lecturer. The result of the research showed that there were some categories of lecturer’s talk performed by the lecturer during classroom interaction, the lecturer applied categories based on FIAC System, and they are: accept feeling, praises and encourages, accepts and uses idea of students, asks questions, lecturing, giving direction, and criticizing or justifying authority. Most frequent category of lecturer’s talk were asking the question, giving direction, praise or encouraging and lecturing.